Alterations in Spectral Attributes of Surface Electromyograms after Utilization of a Foot Drop Stimulator during Post-Stroke Gait - Pilkar, Rakesh; Ramanujam, Arvind; Nolan, Karen J. (Frontiers in Neurology, 2017)
Background: A foot drop stimulator (FDS) is a rehabilitation intervention that stimulates the common peroneal nerve to facilitate ankle dorsiflexion at the appropriate time during post-stroke hemiplegic gait. Time-frequency analysis of nonstationary surface electromyograms (EMG) and spectral variables such as instantaneous mean frequency (IMNF) can provide valuable information on the long term effects of FDS intervention in terms of changes in the motor unit (MU) recruitment during gait, secondary to improved dorsiflexion. Objective: To apply a wavelet based time-frequency analysis approach to assess the changes in neuromuscular activation of the tibialis anterior (TA), soleus (SOL) and gastrocnemius (GA) muscles after utilization of a FDS during gait post stroke. Methods: Surface EMG were collected bilaterally from the TA, SOL and GA muscles from 6 participants (142.9±103.3 months post stroke) while walking without the FDS at baseline and 6 months post FDS utilization. Continuous wavelet transform (CWT) was performed to get the averaged time-frequency distribution of band pass filtered (20-300 Hz) EMGs during multiple walking trials. IMNFs were computed during normalized gait and were averaged during the stance and swing phases. Percent changes in the energies associated with each frequency band of 25 Hz between 25 to 300 Hz were computed and compared between visits. Results: Averaged time-frequency representations of the affected TA, SOL and GA EMG show altered spectral attributes post FDS utilization during normalized gait. The mean IMNF values for the affected TA were significantly lower than the unaffected TA at baseline (p=0.026) and follow up (p=0.038) during normalized stance. The mean IMNF values significantly increased (p=0.017) for the affected GA at follow up during normalized swing. The frequency band of 250-275 Hz significantly increased in the energies post FDS utilization for all muscles. Conclusions: The application of wavelet based time-frequency analysis of EMG and outcome measures (IMNF, energy) extracted from the time-frequency distributions suggest alterations in MU recruitment strategies after the use of FDS in individuals with chronic stroke. This further establishes the efficacy of FDS as a rehabilitation intervention that may promote motor recovery in addition to treating the secondary complications of foot drop due to post-stroke hemiplegia.